Attitudes Toward Mental Health and Help-Seeking Behavior Among Psychology Students at Nusa Cendana University - Salim, Nirmala Karunia; Benu, Juliana Marlin Y.; Pello, Shela Christine; Anakaka, Dian Lestari (Universitas Nusa Cendana, 2024)
This study aims to analyze the relationship between attitudes toward mental health and help-seeking behavior among psychology students at Nusa Cendana University. The participants consisted of 217 active students aged 18-24, selected through purposive sampling. Data were collected using questionnaires measuring attitudes toward mental health and help-seeking behavior, which were then analyzed using Pearson product-moment correlation. The findings indicate that the majority of respondents (77.4%) exhibit a positive attitude toward mental health, while 22.6% hold negative attitudes, reflecting stigma and barriers to help-seeking. The results also demonstrate a significant positive relationship between attitudes toward mental health and help-seeking behavior (r = 0.269; p < 0.05). This suggests that a positive attitude toward mental health contributes to an increased likelihood of students seeking support, whether informally from friends and family or formally from professional services. The study concludes that positive attitudes toward mental health can influence students' help-seeking behavior. The recommendation from this research is to promote ongoing education to reduce stigma and improve mental health literacy, enabling students to seek support more openly when facing mental health challenges. Keywords: attitudes toward mental health, help-seeking behavior, psychology students, Nusa Cendana University, stigma